KONSEP PEMIKIRAN PENDIDIKAN MAHMUD YUNUS: PRESFEKTIF TOKOH PENDIDIKAN BAHASA ARAB - permatasari, indah; Bachtiar , Yusuf; Fachrul , Anis (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
ABSTRACT Philisophy has the significance of profound interest and can likewise be deciphered as a work to investigate the idea of things and accommodate circumstances and logical results. Reasoning is an exceptionally far reaching science and has a great deal to do with regular daily existence, since it very well may be viewed as the fundamental wellspring of all that occurs in this world. The way of thinking of science has had a significant impact in the scholastic world since its introduction to the world and improvement. This exploration utilizes subjective strategies and library techniques are utilized to gather information. The technique utilized is a writing survey or what is typically called a writing audit. The extent of the review investigates reasoning, the place of theory, and its relationship with science. The consequence of this exploration is that way of thinking shows thinking, basic evaluation, inventive critical thinking, and relational abilities. Science is acknowledged as logical truth on the off chance that it meets somewhere around two circumstances: objective and observational.